Digital education community TV existence in post analog switch off - Prihantoro, Edy; Masitoh, Siti; Fatoni, Ahmad; Fitriani, Dinda Rakhma; Ramadhani, Rizky Wulan (ProTVF, 2024)
Background: Based on Law (UU) Number 11 of 2020 regarding Cipta Kerja or the Omnibus Law, broadcasting institutions should switch from terrestrial or analog broadcasts to digital broadcasting via Analog Switch Off (ASO), which provides opportunities for community TV to develop. UGTV is Indonesia’s first digital education community TV to broadcast cultural and education-based programs. Purpose: To analyze the existence of UGTV as the first digital education community TV in Indonesia. Methods: Researchers distributed questionnaires to 144 respondents in Depok and 115 in Bekasi to determine the most popular programs. Researchers then conducted interviews with UGTV staff and leaders and compared the quality of UGTV programs based on KPI standards. Results: Based on the research results, UGTV as Indonesia’s first digital educational community television has met all KPI standards by offering some programs such as Team Teaching and Info Kampus. The types of broadcast programs in the form of tourism and cultural programs are still in demand and influence the audience’s viewing interest. Based on qualitative analysis as a follow-up analysis, the public response in these three areas is currently low because people have many new media choices that can be accessed easily at lower costs. Conclusion: The public feels that television lacks “interesting” shows so the existence of UGTV and other community channels can become a choice for the audience. Implications: KPI and KPID must actively monitor and develop broadcast content by collaborating with community broadcasting institutions so that broadcast production can be more varied.